Book Review: Meade, R. & Dukelow, F. (2015). Defining Events: Power, Resistance and Identity in Twenty-First-Century Ireland, (Concept: The Journal of Contemporary Community Education Practice Theory, 2016)
This publication hooked me from the start with a wonderful, stimulating introduction. The book sets out to analyse and critique twenty-first-century Ireland while ‘consciously avoiding myth making and generalisation’. Examining a wide range of defining events, authors were encouraged to ‘take stock of contexts and contradictions’, ‘think ‘dialectically’’ and not ‘celebrate uncritically or damn unequivocally’. Useful discussions of the concepts of power, resistance and identity set the scene for the chapters to follow but also indicate where readers might expect contributing authors to vary in their understanding of these concepts or the emphases they bring to their analyses.